Tolerance and intolerance in early Judaism and Christianity - Stanton, Graham 1940-2009; Sṭrumzah, Gedalyahu Gʹ. 1948-; Mazal Holocaust Collection (Cambridge Cambridge University Press, 1998)
The essays in this book consider issues of tolerance and intolerance faced by Jews and Christians between approximately 200 BCE and 200 CE. Several chapters are concerned with many different aspects of early Jewish-Christian relationships. Five scholars, however, take a difference tack and discuss how Jews and Christians defined themselves against the pagan world. As minority groups, both Jews and Christians had to work out ways of co-existing with their Graeco-Roman neighbours. Relationships with those neighbours were often strained, but even within both Jewish and Christian circles, issues of tolerance and intolerance surfaced regularly. So it is appropriate that some other contributors should consider 'inner-Jewish' relationships, and that some should be concerned with Christian sects.
Intolerance and martyrdom: from Socrates to Rabbi ʻAqiva / Ithamar Gruenwald. -- The other in 1 and 2 Maccabees / Daniel R. Schwartz. -- The pursuit of the millennium in early Judaism / Albert I. Baumgarten. -- Conservative revolution? The intolerant innovations of Qumran / Michael Mach. -- Who was considered an apostate in the Jewish diaspora? / John M.G. Barclay. -- Why did Paul persecute the church? / Justin Taylor. -- Paul and the limits of tolerance / Stephen C. Barton. -- Philo's views on paganism / Maren R. Niehoff. -- Coexisting with the enemy: Jews and pagans in the Mishnah / Moshe Halbertal. -- Tertullian on idolatry and the limits of tolerance / Guy G. Stroumsa. -- The threefold Christian anti-Judaism / François Blanchetière. -- The intertextual polemic of the Markan vineyard parable / Joel Marcus. -- Jews and Jewish Christians in the land of Israel at the time of the Bar Kochba war, with special reference to the Apocalypse of Peter / Richard Bauckham
The Nazoreans: living at the boundary of Judaism and Christianity / Martinus C. de Boer. -- Justin Martyr's Dialogue with Trypho: group boundaries, 'proselytes' and 'God-fearers' / Graham N. Stanton. -- Accusations of Jewish persecution in early Christian sources, with particular reference to Justin Martyr and the Martyrdom of Polycarp / Judith M. Lieu. -- Early Christians on synagogue prayer and imprecation / William Horbury. -- Messianism, Torah and early Christian tradition / Andrew Chester. -- Jewish and Christian public ethics in the early Roman Empire / Markus Bockmuehl. -- Postscript: the future of intolerance / Guy S. Stroumsa
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Judaism -- History, Post-exilic period, 586 B.C.-210 A.D.; Religious Tolerance -- Judaism; Church history, Primitive and early church, ca. 30-600; Religious Tolerance -- Christianity -- History of doctrines, Early church, ca. 30-600.; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism; Christianity and other religions -- Judaism; Religious Tolerance -- Christianity -- History of doctrines -- Early church, ca. 30-600; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Judaism -- Relations -- Christianity; Religious Tolerance -- Judaism; Church History -- Primitive and early church, ca. 30-600; Judaism ; History ; Post-exilic period, 586 B.C.-210 A.D; Religious tolerance ; Judaism; Church history ; Primitive and early church, ca. 30-600; Religious tolerance ; Christianity ; History of doctrines ; Early church, ca. 30-600; Judaism ; Relations ; Christianity; Christianity and other religions ; Judaism; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Religious Tolerance -- Judaism; Church History -- Primitive and early church, ca. 30-600; Religious Tolerance -- Christianity -- History of doctrines -- Early church, ca. 30-600; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism